2020
DOI: 10.3390/su12093729
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bring-Your-Own-Device Program on Flipped Learning in Higher Education Students

Abstract: The “bring your own device” (BYOD) program is positioned as one of the fastest-emerging methods to solve accessibility problems in the flipped learning methodology. The objective of the study is to analyze the potential of a training plan through inverted learning using the BYOD program compared to inverted learning without BYOD. A quasi-experimental design was carried out on a sample of 118 Higher Education students. A questionnaire was used as an instrument for data collection. The results show that the asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
(73 reference statements)
0
27
0
5
Order By: Relevance
“…The educational process over recent years has evolved to include diverse sources of learning, allowing learners to obtain knowledge from various sources easily. It is clear at the present time that there are developments in teaching methods that depend on technological means [26]. One of the most recent sources of educational learning is via mobile devices, referred to as m-learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The educational process over recent years has evolved to include diverse sources of learning, allowing learners to obtain knowledge from various sources easily. It is clear at the present time that there are developments in teaching methods that depend on technological means [26]. One of the most recent sources of educational learning is via mobile devices, referred to as m-learning.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have employed various acceptance models, such as applying original models, while others employed altered models. One such study found that despite what students may benefit from in relation to the services provided through mobile education and the importance of their acceptance of this type of education, the acceptance of this type of education remains relatively low in some Arab countries [26]. One of the incentives to use mobile education is the ease of access to material regardless of physical constraints and time, especially if there is a high level of confidence of users and that this form of education is compatible with students' devices [27].…”
Section: Related Studies On M-learningmentioning
confidence: 99%
“…Therefore, the guiding research question in this study asks; 'What are the platforms, strategies, tools and techniques, which may support student engagement in art and design education online?'. This article attempts to identify the key factors, engaging pedagogy and supportive techniques able to sustain art and design learning communities in an era of virtual learning portals and digital flipped learning online (Pozo S anchez et al 2020).…”
Section: Studio As a Site For Learning And The Pivot To Online Educationmentioning
confidence: 99%
“…Research of technology‐enabled active learning environments (TE‐ALEs), large student numbers and spatial studies in the changing landscape of education are more ubiquitous (Young & Nichols 2017; Casanova et al 2018; Lee et al 2018; Shi et al 2019). Numerous recent papers seek to examine virtual community of practice (VCoPs), technological platforms and tools in relation to online engagement, such as ‘bring your own device’ (BYOD) programmes, and distributed models of online learning (Chen et al 2020; Peeters & Pretorius 2020; Pozo Sánchez et al 2020). Innovative models for virtual studio learning have been developed by Pektaş (2015) and Jones et al (2020).…”
Section: Studio As a Site For Learning And The Pivot To Online Educationmentioning
confidence: 99%
“…All this promotes profound changes in education, as well as in people's lives and in their daily actions [4]. Furthermore, this is supported by a total increase in the use of technology [5], as the main support for educational innovation today [6]. For this reason, education approaches the idea of a digital society in which students live daily [7].…”
Section: Introductionmentioning
confidence: 99%